2009
DOI: 10.2353/ajpath.2009.080566
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Microchimeric Cells Participate in Tumour Angiogenesis in Melanomas Occurring during Pregnancy

Abstract: Melanoma is a major malignancy in younger individuals that accounts for 8% of all neoplasias associated with gestation. During pregnancy, a small number of fetal cells enter the maternal circulation. These cells persist and then migrate to various maternal tissues where they may engraft and differentiate, particularly if there is organ damage, adopting the phenotype of the host organ. To understand the relationship between melanoma and pregnancy, we analyzed these tumors in both humans and mice. Fetal cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 42 publications
2
68
0
Order By: Relevance
“…These findings along with previous reports, including ours, converge toward the presence of fetal EPCs among the transferred FMCs. 11,12,18,19 Two important questions that we addressed were as follows: were FMCs recruited in high numbers de novo or did randomly transferred FMCs proliferate in situ after tissue injury? Did fetal EPCs respond to specific chemotactic and angiogenic signals as their maternal counterparts?…”
Section: Vegfr2mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings along with previous reports, including ours, converge toward the presence of fetal EPCs among the transferred FMCs. 11,12,18,19 Two important questions that we addressed were as follows: were FMCs recruited in high numbers de novo or did randomly transferred FMCs proliferate in situ after tissue injury? Did fetal EPCs respond to specific chemotactic and angiogenic signals as their maternal counterparts?…”
Section: Vegfr2mentioning
confidence: 99%
“…[5][6][7][8] Fetal microchimeric cells (FMCs) have been identified in larger numbers in pathological conditions, including cancer, inflammatory diseases or reparative processes as compared with normal tissues. [9][10][11][12][13][14][15] This recruitment capacity associated with their described plasticity 7,16 has suggested that the study of fetal cell microchimerism can inform on homing and engraftment of host stem cells in response to tissue injury. We recently investigated whether fetal microchimeric cells contributed to maternal wound healing and used this model to investigate the recruitment of distant EPCs in this process.…”
mentioning
confidence: 99%
“…The mechanism of this association is unclear. In the case of melanoma, microchimeric cells have been suggested to contribute directly to lymphangiogenesis and tumor growth [25]. Because of the multiple factors known to contribute to these cancers over decades of life, the interacting mechanisms involving microchimerism are likely to be elusive.…”
Section: Introductionmentioning
confidence: 99%
“…FMCs selectively home to damaged tissues where they are found in a higher frequency than in uninjured control tissues [6,7]. They can either be a part of the inflammatory infiltrate or integrated into the surrounding maternal tissue, displaying niche-appropriate phenotypes [4,8].…”
mentioning
confidence: 99%